PENGARUH METODE LATIHAN GAYA SELF CHECK TERHADAP KETERAMPILAN GROUNDSTROKE FOREHAND, BACKHAND DAN SERVICE PADA ATLET TENIS SEMEN PADANG - Lolia Manurizal; Muarif Arhas Putra (Program Studi Pendidikan Jasmani, STKIP Bina Bangsa Getsempena, 2017)
Based on the author's observations in the field, that's still a lot of athletes who don't have the basic skills of tennis courts. This can also have a look at match results age group